Emergence of TNIK inhibitors in cancer therapeutics. Issue 5 (24th April 2017) - Yamada, Tesshi; Masuda, Mari
Abstract : The outcome of patients with metastatic colorectal cancer remains unsatisfactory. To improve patient prognosis, it will be necessary to identify new drug targets based on molecules that are essential for colorectal carcinogenesis, and to develop therapeutics that target such molecules. The great majority of colorectal cancers (>90%) have mutations in at least one Wnt signaling pathway gene. Aberrant activation of Wnt signaling is a major force driving colorectal carcinogenesis. Several therapeutics targeting Wnt pathway molecules, including porcupine, frizzled receptors and tankyrases, have been developed, but none of them have yet been incorporated into clinical practice. Wnt signaling is most frequently activated by loss of function of the adenomatous polyposis coli ( APC ) tumor suppressor gene. Restoration of APC gene function does not seem to be a realistic therapeutic approach, and, therefore, only Wnt signaling molecules downstream of the APC gene product can be considered as targets for pharmacological intervention. Traf2 and Nck‐interacting protein kinase (TNIK) was identified as a regulatory component of the β‐catenin and T‐cell factor‐4 (TCF‐4) transcriptional complex. Several small‐molecule compounds targeting this protein kinase have been shown to have anti‐tumor effects against various cancers. An anthelmintic agent, mebendazole, was recently identified as a selective inhibitor of TNIK and is under clinical evaluation. TNIK regulates Wnt signaling in the most downstream part of the pathway, and its pharmacological inhibition seems to be a promising therapeutic approach. We demonstrated the feasibility of this approach by developing a small‐molecule TNIK inhibitor, NCB‐0846. Abstract : Knockdown of TNIK inhibits the growth of colorectal cancer cells and xenografts.